2019
DOI: 10.4102/sajhivmed.v20i1.1008
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment at 11 months after starting antiretroviral therapy within 3 weeks of life

Abstract: BackgroundAntiretroviral therapy (ART) started between 7 and 12 weeks of age improves neurodevelopmental outcomes in HIV-infected (HIV+) infants, but the impact of even earlier initiation is not yet described.ObjectivesWe assessed the early neurodevelopment of HIV+ infants who started ART within 21 days of life.MethodParticipants were enrolled from the public sector birth HIV-diagnosis programme. Inclusion criteria included the following: birth weight > 2000 g, infant commencing ART < 6 weeks and no infant cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…At 12 months of age, children in the OG achieved good BSID-III scores, which were all within 1 SD of the test reference mean. Similar results, from a 2019 South African cohort of HEI infants starting ART within 3 weeks of life and assessed using the Griffiths Mental Development Scale at a mean age of 11.5 ± 0.8 months, reported infants to achieve scores within the normal range (Laughton et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…At 12 months of age, children in the OG achieved good BSID-III scores, which were all within 1 SD of the test reference mean. Similar results, from a 2019 South African cohort of HEI infants starting ART within 3 weeks of life and assessed using the Griffiths Mental Development Scale at a mean age of 11.5 ± 0.8 months, reported infants to achieve scores within the normal range (Laughton et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…Undoubtably, the key issue in neuropsychological function preservation in children is early HIV diagnosis and treatment, ideally through birth diagnosis or within the first few weeks of life. Not only does this limit HIV-encephalopathy and neurocognitive impairment, but also all the comorbidities associated with untreated HIV infection ( 6 , 7 , 54 ). Brain structure and integrity are central to neurocognitive development and neuroimaging studies have shown a number of abnormalities in CALHIV that can explain these deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Early ART initiation has a substantial positive impact on neurocognitive function (6,7). Numerous studies report worse neuropsychological outcomes in CLHIV than HIVuninfected children and adolescents, specifically regarding executive functioning (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The early initiation of ART in infants has been shown to reduce morbidity and mortality and to improve neurodevelopmental outcomes; therefore, it is of paramount importance to educate mothers on the significance of followup visits. 15…”
Section: Discussionmentioning
confidence: 99%